Gamification and Customer Churn among Millennials in Klang Valley: The Mediating Role of Loyalty and Brand Attractiveness - Si, Chong En (2025)
In the competitive and increasingly digitalised business environment today, customer retention has become a critical concern, particularly among Millennials who demonstrate high churn tendencies and strong digital expectations. This study investigates the impact of gamification elements on customer churn, with loyalty and brand attractiveness as mediators, among Millennials in the Klang Valley, Malaysia. Grounded in the Stimulus-Organism-Response (S-O-R) model, Customer Engagement Theory, Self-Determination Theory (SDT), and gamification frameworks such as Bartle’s Player Types and Yee’s Player Motivation Model, the research examines how specific gamification strategies influence consumer behaviour. Based on a quantitative research design, a structured questionnaire was administered to 180 millennial respondents. The Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyse the structural relationships among variables, given its suitability for predictive modelling and small-to-medium sample sizes. The gamification elements evaluated include membership programmes, discounts, contest rewards, and digitalised content. The findings showed that digitalised content significantly influences both customer loyalty and brand attractiveness. However, membership programmes exhibited no significant direct effect, while discounts and contest rewards showed limited influence. Among the mediators, brand attractiveness demonstrated a stronger effect in reducing customer churn compared to loyalty. The model exhibited good predictive accuracy, with Q² values exceeding the accepted thresholds for all key constructs. These results have highlighted the importance of personalised and interactive gamification strategies in retaining Millennial customers. Businesses are advised to prioritise digital content and contest-based engagement to enhance brand attractiveness and loyalty. Future research is recommended to investigate the long term effectiveness of gamification and explore emerging technologies such as augmented and virtual reality for customer engagement.